2022
DOI: 10.32942/osf.io/kevqp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeatability of performance within and across contexts measuring behavioral flexibility

Abstract: Research into animal cognitive abilities is increasing quickly and often uses methods where behavioral performance on a task is assumed to represent variation in the underlying cognitive trait. However, because these methods rely on behavioral responses as a proxy for cognitive ability, it is important to validate that the task structure does, in fact, target the cognitive trait of interest rather than non-target cognitive, personality, or motivational traits (construct validity). One way to validate that task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…If an individual did not approach within 20 cm, it was given a latency of 2701 sec (45 min plus 1 sec). In a previous experiment (McCune et al, 2019b), we validated that grackles did not perceive the novel environment as threatening (i.e., it was not a measure of boldness). Experimental protocol (see Supplementary Material 5 for more details).…”
Section: Average Number Of Generations Citationmentioning
confidence: 70%
See 2 more Smart Citations
“…If an individual did not approach within 20 cm, it was given a latency of 2701 sec (45 min plus 1 sec). In a previous experiment (McCune et al, 2019b), we validated that grackles did not perceive the novel environment as threatening (i.e., it was not a measure of boldness). Experimental protocol (see Supplementary Material 5 for more details).…”
Section: Average Number Of Generations Citationmentioning
confidence: 70%
“…However, the Tempe grackles responded differently to the novel environment and novel object, therefore they did not perceive the stimuli as the same. From the Tempe grackle data, we found that responses were only repeatable for the novel environment test (McCune et al, 2019b). Therefore, we conducted this assay (and not the novel object assay) with the Woodland grackles and compared the two populations on this one assay.…”
Section: Post-study Choices Made Since Receiving In Principle Recomme...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we use a likelihood ratio test to compare a mixed model to a model without the ID random effect, and the function rpt from the package: rptR (Stoffel et al, 2017) to estimate the variance in the dependent variable attributable to consistent differences among individuals across the two tests. We previously found that this method produces the same repeatability results as the MCMCglmm method using a Gaussian distribution (K. McCune et al, 2022).…”
Section: Post-study Choices Made Since Receiving In Principle Recomme...mentioning
confidence: 84%
“…The change in the rate of deviation during the manipulation might indicate that individuals learned about the serial nature of the reversal experiment, that they should deviate from their previous attractions as soon as the reward changes. While there were individual differences in learning and deviation rates(McCune et al, 2022), all individuals appeared to change depending on their experiences. The manipulation pushed individuals to levels that were already observed in some individuals at the beginning of the experiment, suggesting that individuals might also change their behavioral flexibility in response to their experiences in their natural habitats.…”
mentioning
confidence: 95%